प्रमास्वरूपं तद्भेदाश्च [Pramaswaroopam tadbhedaashcha] - आचार्यः Acharya, पुरुषोत्तम Purushottam (Haimaprabha, 2021)
नेपाली भाषामा सारंश लेख संगै उपलब्ध छ [Nepali language abstracts available with article] [The presented article includes an in-depth discussion of Prama form the perspective of NyayaDarshan and VaisheshikDarshan in Eastern Philosophy. In the process of differentiating the form and aspects of Prama, NyayaDarshan mentions major four types of Prama; Pratyaksha, Anumiti, Upamiti, and Shaabda while VaisheshikDarshan mentions two types of Prama; Pratyakshaand Anumiti. This paper has been prepared following the existing theoretical bases and qualitative research methodology. Article concludes TadwatiTatprakarkaanubhava is itself Prama and in-depth discussion of Prama as the form of true knowledge has been mentioned. From the perspective of VaisheshikDarshan, Upamiti and ShaabaPramahavebeen assumed as the Anumiti and integrated within Anuman. This article is expected to be useful for the readers interested in Prama mentioned in NyayaDarshan and Vaisheshik Darshan.]